Effects of school start times and technology use on teenagers' sleep: 1999–2008. Issue 1 (18th January 2013) - Borlase, Brigid Jane; Gander, Philippa Helen; Gibson, Rosemary Helen
Abstract: This study compared sleep patterns of high school students in 1999 and 2008. In 2006, school start times were delayed for senior students (years 12–13) from 09:00 to 10:30. For junior students (years 9–11), start time remained unchanged at 09:00. Questionnaires were completed at school by 212 year 9 and 12 students in 1999, and 455 year 9, 11 and 12 students in 2008. Year 12 students in 2008 were less likely to report sleep loss on school nights (OR = 0.06, 95% CI = 0.01–0.11) and were less sleepy (OR = 0.58, 95% CI = 0.34–0.98) than Year 12 in 1999 or than Year 11 in 2008, after controlling for gender (sleep loss, OR = 0.31, 95%CI = 0.19–0.53; sleepiness, OR = 0.46, 95% CI = 0.28–0.75). There were no comparable changes for Year 9 students. From 1999–2008, students having technologies in the bedroom rose from 80.7% to 96.4% ( P (χ 2 ) < 0.001). In 2008, having more technologies was associated with less sleep on school nights (Spearman's rho P = 0.005). In 2008, Year 9 students with more technologies were more likely to report daytime sleepiness (OR = 4.06, 95% CI = 1.44–11.41) and being evening type (OR = 3.38, 95% CI = 1.27–9.01), after controlling for gender. In 2008 all year groups went to bed earlier than in 1999, possibly due to increased sleep awareness, but only Year 12 students sleep later on school mornings. We conclude that delaying school start time had beneficial effects for Year 12 students, reducing sleep loss on school nights and daytime sleepiness. However, increased presence of technologies is associated with later sleep times and daytime sleepiness among Year 9 students.